The herbicides glyphosate and glufosinate and the cyanotoxin β-N-methylamino-l-alanine induce long-term motor disorders following postnatal exposure: the importance of prior asymptomatic maternal inflammatory sensitization - Oummadi, Asma; Menuet, Arnaud; Méresse, Sarah; Laugeray, Anthony; Guillemin, Gilles; Mortaud, Stéphane (Frontiers in Neuroscience, 2023)
Background Prenatal maternal immune activation (MIA) and/or perinatal exposure to various xenobiotics have been identified as risk factors for neurological disorders, including neurodegenerative diseases. Epidemiological data suggest an association between early multi-exposures to various insults and neuropathologies. The “multiple-hit hypothesis” assumes that prenatal inflammation makes the brain more susceptible to subsequent exposure to several kinds of neurotoxins. To explore this hypothesis and its pathological consequences, a behavioral longitudinal procedure was performed after prenatal sensitization and postnatal exposure to low doses of pollutants. Methods Maternal exposure to an acute immune challenge (first hit) was induced by an asymptomatic lipopolysaccharide (LPS) dose (0.008 mg/kg) in mice. This sensitization was followed by exposing the offspring to environmental chemicals (second hit) postnatally, by the oral route. The chemicals used were low doses of the cyanotoxin β-N-methylamino-l-alanine (BMAA; 50 mg/kg), the herbicide glufosinate ammonium (GLA; 0.2 mg/kg) or the pesticide glyphosate (GLY; 5 mg/kg). After assessing maternal parameters, a longitudinal behavioral assessment was carried out on the offspring in order to evaluate motor and emotional abilities in adolescence and adulthood. Results We showed that the low LPS immune challenge was an asymptomatic MIA. Even though a significant increase in systemic pro-inflammatory cytokines was detected in the dams, no maternal behavioral defects were observed. In addition, as shown by rotarod assays and open field tests, this prenatal LPS administration alone did not show any behavioral disruption in offspring. Interestingly, our data showed that offspring subjected to both MIA and post-natal BMAA or GLA exposure displayed motor and anxiety behavioral impairments during adolescence and adulthood. However, this synergistic effect was not observed in the GLY-exposed offspring. Conclusion These data demonstrated that prenatal and asymptomatic immune sensitization represents a priming effect to subsequent exposure to low doses of pollutants. These double hits act in synergy to induce motor neuron disease-related phenotypes in offspring. Thus, our data strongly emphasize that multiple exposures for developmental neurotoxicity regulatory assessment must be considered. This work paves the way for future studies aiming at deciphering cellular pathways involved in these sensitization processes.